Improving medication adherence with adjuvant aromatase inhibitor in women with breast cancer: A randomised controlled trial to evaluate the effect of short message service (SMS) reminder - Eng Hooi Tan; Andrea Li Ann Wong; Chuan Chien Tan; Patrick Wong; Sing Huang Tan; Li En Yvonne Ang; Siew Eng Lim; Wan Qin Chong; Jingshan Ho; Soo Chin Lee; Bee Choo Tai (Breast, 2020)
Background: Medication adherence is crucial for improving clinical outcomes in the treatment of patients. We evaluate the effect of short message service (SMS) reminder on medication adherence and serum hormones in patients with breast cancer on aromatase inhibitors. Methods: An open-label, multi-centre, prospective randomised controlled trial of SMS versus Standard Care was conducted. Medication adherence was assessed via self-report using the Simplified Medication Adherence Questionnaire at baseline, 6 month, and 1 year. Androstenedione, estradiol, and estrone were measured at baseline and 1 year. The χ2 test and mixed effects logistic regression was performed to compare medication adherence between groups. Difference in androstenedione and estrone levels were assessed using analysis of covariance, whereas χ2 test and logistic regression was used for estradiol. Analysis was based on intention-to-treat. Results: A total of 244 patients were randomised to receive weekly SMS reminder (n = 123) or Standard Care (n = 121) between May 2015 and December 2018. The odds of adherence was higher at 6-month in SMS (OR = 1.78, 95% CI 1.04–3.05, p = 0.034), and not significantly different at 1-year (OR = 1.15, 95% CI: 0.67–1.96 p = 0.617). Mixed effects logistic regression analysis showed higher odds of adherence in SMS over the 1-year period (OR = 2.35, 95% CI: 1.01–5.49, p = 0.048). There was no difference in serum hormone levels between groups. Conclusion: SMS reminder improved medication adherence in the short-term but had no effect on serum hormones levels in the longer term. Future studies could investigate the use of tailored SMS intervention according to patient preference to improve its sustainability.